Acute Onset Polymyositis after Prolactinoma Extirpation - Juan Jakez-Ocampo; Yemil Atisha-Fregoso; Luis Llorente (Case Reports in Rheumatology, 2014)
Hyperprolactinemia has been related to autoimmune diseases. Herein, we describe a case of a female with a prolactin producer pituitary macroadenoma who developed severe polymyositis one month after its removal. The patient had very high levels of CPK and muscle biopsy showed remarkable inflammatory infiltration. Steroid therapy was followed with total recovery. To the best of our knowledge, this is the first case reported of acute polymyositis after pituitary macroadenoma exeresis.